527. New Robust Antimicrobial Stewardship Program (ASP) Results in Reduction of Clostridium difficile 30-Day Readmission. (26th November 2018) - Anthone, Jennifer; Abbas, Anum; Alexander, Bryan; Boldt, Dayla; Ased, Sumaya; Carroll, Cassara; Cavalieri, Stephen; Horne, John; Velagapudi, Manasa; Valenta, Carrie; Andukuri, Giri; Paguia, Richard Albert; et al.
Abstract: Background: As the pipeline for antibiotics is decreasing and antibiotic resistance is increasing, it is critically important to be stewards of antibiotics. ASP has become a mandated program as of January of 2017 by Joint Commission and condition of participation for CMS on reimbursement. A pilot program of C. difficile treatment in the academic medical center proved to be quite useful to adapt to a larger healthcare system. Methods: A dedicated Infectious Disease physician and three Antibiotics stewardship pharmacists (ASP) were hired to run this program. Goals of the program was to decrease broad-spectrum antibiotics use, and reduce Clostridium difficile readmission (CDR) for the healthcare system. Performance of CDR for each inpatient was accomplished with ASP making recommendations for treatment. Queries were built into the ASP software and alerts were generated in the electronic medical record (EMR). CDR was targeted daily for ASP pharmacists/ID physician. Comparison of fiscal year 2017 (control group) with 2018 (intervention group) was performed. Results: CDR was reduced (control group 17.53% vs. intervention group 14.12%), respectively, for our healthcare system ( P > 0.05). However, overall cost savings for the healthcare system was $1.3 million was realized. In the academic medical center specifically, with over 400 beds there was a significant reduction in CDR (control group 21% to intervention group 10.5% ( P < 0.05). Cost savings estimated from CDR were $610, 923. Finally, length of stay was reduced by 1 day for inpatients with C. difficile admission in the academic medical center. Conclusion: ASP not only has immediate impact on patient care and safety but also can play a large role in treating the appropriate disease state and reduces unnecessary readmission to the acute care hospitals in our healthcare system. Disclosures: All authors: No reported disclosures.